Learning the Nuclear Educational Tourism in (Post)Industrial Sites - Mazeikiene, Natalija (Peter Lang International Academic Publishing Group, 2021)
This book illuminates the educational potential of nuclear tourism and learning about nuclear power in informal and non-formal learning settings. The authors present a case of elaboration of the educational virtual nuclear route in the Ignalina Power Plant Region, Lithuania. Nuclear tourism takes its shape at the junction of several types of tourism - energy, industrial, cultural, and heritage and it becomes a site of outdoor and place-based education, promotes STEM, energy literacy, critical thinking, and environmental skills, and creates a valuable source for virtual learning. The book reveals peculiarities of learning and experience at nuclear power plants and disaster tourism destinations such as the Chernobyl Museum and the Chernobyl Exclusion Zone.